2014
DOI: 10.1016/j.bone.2014.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Jagged1 is essential for osteoblast development during maxillary ossification

Abstract: Maxillary hypoplasia occurs due to insufficient maxillary intramembranous ossification, leading to poor dental occlusion, respiratory obstruction and cosmetic deformities. Conditional deletion of Jagged1 (Jag1) in cranial neural crest (CNC) cells using Wnt1-cre; Jagged1f/f (Jag1CKO) led to maxillary hypoplasia characterized by intrinsic differences in bone morphology and density using μCT evaluation. Jag1CKO maxillas had altered collagen deposition, delayed ossification, and reduced expression of early and lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 30 publications
3
46
0
1
Order By: Relevance
“…ARS was quantified as described. (15) The samples were read on a Flex Station 3 microplate reader (Molecular Devices, Sunnyvale, CA, USA) at 405 nm in 96-well opaque-walled transparent-bottomed plates. Data were collected with Soft Max Pro (Molecular Devices) software.…”
Section: Methodsmentioning
confidence: 99%
“…ARS was quantified as described. (15) The samples were read on a Flex Station 3 microplate reader (Molecular Devices, Sunnyvale, CA, USA) at 405 nm in 96-well opaque-walled transparent-bottomed plates. Data were collected with Soft Max Pro (Molecular Devices) software.…”
Section: Methodsmentioning
confidence: 99%
“…While endothelial Notch activity was reported as an essential source for the coordinated osteogenesis and angiogenesis during the bone development [44], it is not clear if it's necessary to include endothelial progenitors in engineered bone tissues to achieve Notch-induced angiogenesis. It was reported that the expression of Notch ligand Jaggedl was able to induce osteogenesis [78], whereas the genetic deletion of Jaggedl resulted in defects in osteoblast development and differentiation during maxillary ossification [79]. We previously found that the downstream target gene of Notch signaling Heyl was upregulated by BMP9 [28], suggesting BMP9 may act upstream of Notch signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of this complex was observed and found to be important for endothelial function and neuroepithelial cell differentiation [118, 119]. Follow up work has now determined that crosstalk between Notch and BMP is important for a wide variety of cellular responses including osteoblastic differentiation [120-122] and vascular biology/angiogenesis [123, 124]. Finally, besides TGF-β and BMP, little is known regarding crosstalk between other TGF-β superfamily members and Notch.…”
Section: Notch and Tgf-βmentioning
confidence: 99%